Gaze characteristics of elite and near-elite athletes in ice hockey defensive tactics - Martell, S. G.; Vickers, J. N. (Human Movement Science, 2004)
Traditional visual search experiments, where the researcher pre-selects video-based scenes for the participant to respond to, shows that elite players make more efficient decisions than non-elites, but disagree on how they temporally regulate their gaze. Using the vision-in-action [J.N. Vickers, J. Exp. Psychol.: Human Percept. Perform. 22 (1996) 342] approach, we tested whether the significant gaze that differentiates elite and non-elite athletes occurred either: early in the task and was of more rapid duration [A.M. Williams et al., Res. Quart. Exer. Sport 65 (1994) 127; A.M. Williams and K. Davids, Res. Quart. Exer. Sport 69 (1998) 111], or late in the task and was of longer duration [W. Helsen, J.M. Pauwels, A cognitive approach to visual search in sport, in: D. Brogan, K. Carr (Eds.), Visual Search, vol. II, Taylor and Francis, London, 1992], or whether a more complex gaze control strategy was used that consisted of both early and rapid fixations followed by a late fixation of long duration prior to the final execution. We tested this using a live defensive zone task in ice hockey. Results indicated that athletes temporally regulated their gaze using two different gaze control strategies. First, fixation/tracking (F/T) gaze early in the trial were significantly shorter than the final F/T and confirmed that the elite group fixated the tactical locations more rapidly than the non-elite on successful plays. And secondly, the final F/T prior to critical movement initiation (i.e. F/T-1) was significantly longer for both groups, averaging 30% of the final part of the phase and occurred as the athletes isolated a single object or location to end the play. The results imply that expertise in defensive tactics is defined by a cascade of F/T, which began with the athletes fixating or tracking specific locations for short durations at the beginning of the play, and concluded with a final gaze of long duration to a relatively stable target at the end. The results are discussed within the context of gaze research in open and closed skills, as well as theoretical models of long-term memory and decision making in sport.